Literature Review : Faktor Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Karyawan Rumah Sakit - Abiyusa, Annisaa Yuniarti; Hariyono, Widodo; Hidayat, Muhammad Syamsu (Syntax Corporation, 2025)
Employee performance is a crucial factor in determining the success and sustainability of an organization, including hospitals. This study aims to examine the influence of Occupational Health and Safety (OHS) on employee performance in hospitals. The method used is a systematic review following the PRISMA approach. Data sources were obtained from Google Scholar and PubMed using keywords related to factors affecting employee performance. The selected articles were published between 2019 and 2023 and available in full text. The review found that several factors significantly influence employee performance, including work motivation, work environment, work discipline, OHS, workload, and job stress. Employee performance improves with better motivation, a conducive work environment, proper implementation of OHS, discipline, and manageable workloads. On the other hand, job stress has a negative impact on employee performance. Therefore, effective implementation of Occupational Health and Safety systems plays a vital role in improving productivity and performance among hospital staff.